1990
DOI: 10.1007/bf00236710
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sport (football) on growth auxological, anthropometric and hormonal aspects

Abstract: There are very few data available on the relationship between sporting activities, endocrine levels and changes in anthropometric measurements during growth. In order to study these relationships, we have made measurements of growth, changes in physical conformation and the plasma levels of several hormones [cortisol, dehydroepiandrosterone sulphate (DHEA-S), testosterone, growth hormone, somatomedin C, insulin, glycaemia and haemoglobin A1C] in 175 boys, aged 10-16 years, who have played football at a competi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0
2

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 25 publications
5
24
0
2
Order By: Relevance
“…On the other hand, the early maturation in soccer players during puberty which recognized in European players (Cacciari et al, 1990;Malina et al, 2000) was also recognized in Japanese youth soccer players with J-SA. Especially between U12 and U13 age category, the cross-sectional diŠerence was remarkably in J-SA (1.7 years) and TW3 (2.6 years) comparing to those of annual increment value (1.1 years and 1.5 years, respectively).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…On the other hand, the early maturation in soccer players during puberty which recognized in European players (Cacciari et al, 1990;Malina et al, 2000) was also recognized in Japanese youth soccer players with J-SA. Especially between U12 and U13 age category, the cross-sectional diŠerence was remarkably in J-SA (1.7 years) and TW3 (2.6 years) comparing to those of annual increment value (1.1 years and 1.5 years, respectively).…”
Section: Discussionmentioning
confidence: 85%
“…However, when selecting the youth players, their subjective assessment biased toward the early biological maturation such as skeletal age, because it strongly correlates to a development of motor ability (Beunen et al, 1997a, b), and sometimes soccer skill . Thus, it has been reported that this bias result in the skewed distribution of maturation in same chronological age category; ie, Skeletal age (SA) of most player in post-puberty advances compared to chronological age (CA), conversely in pre-puberty SA tends to be lower than CA (Cacciari et al, 1990;Malina et al, 2000, Hirose, 2009.…”
Section: Introductionmentioning
confidence: 99%
“…The highest reduction in skin folds from year to year is seen in the lower limb, which is probably a result of the training process and competitions. Cacciari et al (1990) have come to results that players in puberty of 12 and 14 y had smaller skin folds (triceps and sub-scapula) than inactive controlled group. These differences support the suggestions that physical training can lead to increased muscle and reduce body fat (Cacciari et al).…”
Section: Discussionmentioning
confidence: 99%
“…This difference declines when adulthood is reached (Beunen et al, 1997;Cacciari et al, 1990;Hansen et al, 1999a). Williams and Reilly (2000b) suggested that the physical characteristics of players are related to performance.…”
Section: A) Physical Predictorsmentioning
confidence: 99%
“…Furthermore, a relationship was found between maturation, haemoglobin concentrations as well as with the development of aerobic power. Cacciari et al (1990) investigated the effects of soccer on anthropometrical and hormonal aspects of growth. The 399 Italian boys who participated in this cross-sectional study consisted of two groups.…”
Section: B) Studies On Physiological Predictorsmentioning
confidence: 99%